Examine The Factors That Affect The Return to Bidder and Target Company Surrounding The Merger and Acquisition Announcements - Yeung, Shun Tony (2006)
As we understand the effect of merger and acquisition (M&A) from the five big M&A waves in the market. It is useful to have some kind of research activity on the profitability of M&A, as both bidders and target firms will interest it. Therefore the primary objective for this study will be to examine the impact of mergers and acquisition on the returns to the shareholders of both bidder and target firms surrounding the announcement days. We will use four different results to examine that (market & market-adjusted models with either industry or broad benchmarks). Our results conclude that that target firm should normally have a positive return, and the bidder's return evidence is not too clear, so we assume that to be zero. Also the merger announcement news and information is relatively efficient to take effect on the stock price. In the method of exchange, our result shows that the target firm will earn the most on the announcement date in cash deal, followed by mixed deal and finally stock deal.